Clinical Outcomes of Surgical Management of Primary Brachial Plexus Tumors - Gaba, Sunil; Mohsina, Subair; John, Jerry R.; Tripathy, Satyaswarup; Sharma, Ramesh Kumar (Indian Journal of Plastic Surgery, 2021)
Introduction This study evaluates the clinical presentation, tumor characteristics, and clinical outcomes of surgically treated benign and malignant brachial plexus tumors (BPTs).Methods A prospective study of patients with BPTs from June 2015 to August 2020 was conducted. All patients underwent surgical resection with microneurolysis and intraoperative electrical stimulation to preserve the functioning nerve fascicles.Results Fourteen patients with 15 BPTs underwent surgical resection. Mean age was 37.8 ± 12.3 years; with male to female ratio 4:10. The clinical presentations were swelling (100%), pain (84.6%), and paresthesia (76.9%). The lesions involved roots (5/15), trunk (5/15), division (1/15), and cords (4/15). Thirteen patients had benign pathology (8 schwannomas, 3 neurofibromas, 2 lipomas) and two had malignant neurofibrosarcoma. Gross total resection was achieved in all cases except a dumbbell tumor. The mean follow-up period was 24 ± 5 months. Postoperatively, all patients reported improvement in pain and paresthesia with no new sensory deficit. All patients had developed initial motor weakness (Grades 2–4); however, full power (Grade 5) was recovered by 3 to 5 months.Conclusion Total resection can be achieved by appropriate microneural dissection and electrophysiologic monitoring and is potentially curative with preserving function.
Keywords: schwannoma; neurofibroma; microneurolysis; paresthesia; dumbbell tumor